Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Detection and attribution of an anomaly in terrestrial photosynthesis in Europe during the COVID-19 lockdown - Angela Che Ing Tang; Christophe R. Flechard; Nicola Arriga; Dario Papale; Paul C. Stoy; Nina Buchmann; Matthias Cuntz; John Douros; Silvano Fares; Alexander Knohl; Ladislav Šigut; Guillaume Simioni; et al. (Science of The Total Environment, 2023)

Uncovering the critical soil moisture thresholds of plant water stress for European ecosystems - Zheng Fu; Philippe Ciais; David Makowski; Ana Bastos; Paul C. Stoy; Andreas Ibrom; Alexander Knohl; Mirco Migliavacca; Matthias Cuntz; Ladislav Šigut; Matthias Peichl; Denis Loustau; et al. (Global Change Biology, 2022)
Understanding the critical soil moisture (SM) threshold (θ crit ) of plant water stress and land surface energy partitioning is a basis to evaluate drought impacts and improve models for predicting future ecosystem condition and climate. Quantifying the θ crit across biomes and climates is challenging because observations of surface energy fluxes and SM remain sparse. Here, we used the latest database of eddy covariance measurements to estimate θ crit across Europe by evaluating evaporative fraction (EF)‐SM relationships and investigating the covariance between vapor pressure deficit (VPD) and gross primary production (GPP) during SM dry‐down periods. We found that the θ crit and soil matric potential threshold in Europe are 16.5% and −0.7 MPa, respectively. Surface energy partitioning characteristics varied among different vegetation types; EF in savannas had the highest sensitivities to SM in water‐limited stage, and the lowest in forests. The sign of the covariance between daily VPD and GPP consistently changed from positive to negative during dry‐down across all sites when EF shifted from relatively high to low values. This sign of the covariance changed after longer period of SM decline in forests than in grasslands and savannas. Estimated θ crit from the VPD–GPP covariance method match well with the EF–SM method, showing this covariance method can be used to detect the θ crit . We further found that soil texture dominates the spatial variability of θ crit while shortwave radiation and VPD are the major drivers in determining the spatial pattern of EF sensitivities. Our results highlight for the first time that the sign change of the covariance between daily VPD and GPP can be used as an indicator of how ecosystems transition from energy to SM limitation. We also characterized the corresponding θ crit and its drivers across diverse ecosystems in Europe, an essential variable to improve the representation of water stress in land surface models.

Dissolved carbon leaching from soil is a crucial component of the net ecosystem carbon balance - REIMO KINDLER; JAN SIEMENS; KLAUS KAISER; DAVID C. WALMSLEY; CHRISTIAN BERNHOFER; NINA BUCHMANN; PIERRE CELLIER; WERNER EUGSTER; GERD GLEIXNER; THOMAS GRŨNWALD; ALEXANDER HEIM; ANDREAS IBROM; et al. (Global Change Biology, 2011)
Estimates of carbon leaching losses from different land use systems are few and their contribution to the net ecosystem carbon balance is uncertain. We investigated leaching of dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and dissolved methane (CH 4 ), at forests, grasslands, and croplands across Europe. Biogenic contributions to DIC were estimated by means of its δ 13 C signature. Leaching of biogenic DIC was 8.3±4.9 g m −2 yr −1 for forests, 24.1±7.2 g m −2 yr −1 for grasslands, and 14.6±4.8 g m −2 yr −1 for croplands. DOC leaching equalled 3.5±1.3 g m −2 yr −1 for forests, 5.3±2.0 g m −2 yr −1 for grasslands, and 4.1±1.3 g m −2 yr −1 for croplands. The average flux of total biogenic carbon across land use systems was 19.4±4.0 g C m −2 yr −1 . Production of DOC in topsoils was positively related to their C/N ratio and DOC retention in subsoils was inversely related to the ratio of organic carbon to iron plus aluminium (hydr)oxides. Partial pressures of CO 2 in soil air and soil pH determined DIC concentrations and fluxes, but soil solutions were often supersaturated with DIC relative to soil air CO 2 . Leaching losses of biogenic carbon (DOC plus biogenic DIC) from grasslands equalled 5–98% (median: 22%) of net ecosystem exchange (NEE) plus carbon inputs with fertilization minus carbon removal with harvest. Carbon leaching increased the net losses from cropland soils by 24–105% (median: 25%). For the majority of forest sites, leaching hardly affected actual net ecosystem carbon balances because of the small solubility of CO 2 in acidic forest soil solutions and large NEE. Leaching of CH 4 proved to be insignificant compared with other fluxes of carbon. Overall, our results show that leaching losses are particularly important for the carbon balance of agricultural systems.

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)
Overviewing the European carbon (C), greenhouse gas (GHG), and non‐GHG fluxes, gross primary productivity (GPP) is about 9.3 Pg yr −1 , and fossil fuel imports are 1.6 Pg yr −1 . GPP is about 1.25% of solar radiation, containing about 360 × 10 18 J energy – five times the energy content of annual fossil fuel use. Net primary production (NPP) is 50%, terrestrial net biome productivity, NBP, 3%, and the net GHG balance, NGB, 0.3% of GPP. Human harvest uses 20% of NPP or 10% of GPP, or alternatively 1‰ of solar radiation after accounting for the inherent cost of agriculture and forestry, for production of pesticides and fertilizer, the return of organic fertilizer, and for the C equivalent cost of GHG emissions. C equivalents are defined on a global warming potential with a 100‐year time horizon. The equivalent of about 2.4% of the mineral fertilizer input is emitted as N 2 O. Agricultural emissions to the atmosphere are about 40% of total methane, 60% of total NO‐N, 70% of total N 2 O‐N, and 95% of total NH 3 ‐N emissions of Europe. European soils are a net C sink (114 Tg yr −1 ), but considering the emissions of GHGs, soils are a source of about 26 Tg CO 2 C‐equivalent yr −1 . Forest, grassland and sediment C sinks are offset by GHG emissions from croplands, peatlands and inland waters. Non‐GHGs (NH 3 , NO x ) interact significantly with the GHG and the C cycle through ammonium nitrate aerosols and dry deposition. Wet deposition of nitrogen (N) supports about 50% of forest timber growth. Land use change is regionally important. The absolute flux values total about 50 Tg C yr −1 . Nevertheless, for the European trace‐gas balance, land‐use intensity is more important than land‐use change. This study shows that emissions of GHGs and non‐GHGs significantly distort the C cycle and eliminate apparent C sinks.

Artificial drainage and associated carbon fluxes (CO 2 /CH 4 ) in a tundra ecosystem - L. MERBOLD; W. L. KUTSCH; C. CORRADI; O. KOLLE; C. REBMANN; P. C. STOY; S. A. ZIMOV; E.‐D. SCHULZE (Global Change Biology, 2009)
Ecosystem flux measurements using the eddy covariance (EC) technique were undertaken in 4 subsequent years during summer for a total of 562 days in an arctic wet tundra ecosystem, located near Cherskii, Far‐Eastern Federal District, Russia. Methane (CH 4 ) emissions were measured using permanent chambers. The experimental field is characterized by late thawing of permafrost soils in June and periodic spring floods. A stagnant water table below the grass canopy is fed by melting of the active layer of permafrost and by flood water. Following 3 years of EC measurements, the site was drained by building a 3 m wide drainage channel surrounding the EC tower to examine possible future effects of global change on the tundra tussock ecosystem. Cumulative summertime net carbon fluxes before experimental alteration were estimated to be about +15 g C m −2 (i.e. an ecosystem C loss) and +8 g C m −2 after draining the study site. When taking CH 4 as another important greenhouse gas into account and considering the global warming potential (GWP) of CH 4 vs. CO 2 , the ecosystem had a positive GWP during all summers. However CH 4 emissions after drainage decreased significantly and therefore the carbon related greenhouse gas flux was much smaller than beforehand (475 ± 253 g C‐CO 2 ‐e m −2 before drainage in 2003 vs. 23 ± 26 g C‐CO 2 ‐e m −2 after drainage in 2005).

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Use of remotely sensed land use classification for a better evaluation of micrometeorological flux measurement sites - L. M. Reithmaier; M. Göckede; T. Markkanen; A. Knohl; G. Churkina; C. Rebmann; N. Buchmann; T. Foken (Theoretical and Applied Climatology, 2006)

Quality analysis applied on eddy covariance measurements at complex forest sites using footprint modelling - C. Rebmann; M. Göckede; T. Foken; M. Aubinet; M. Aurela; P. Berbigier; C. Bernhofer; N. Buchmann; A. Carrara; A. Cescatti; R. Ceulemans; R. Clement; et al. (Theoretical and Applied Climatology, 2005)

Forest and agricultural land‐use‐dependent CO 2 exchange in Thuringia, Germany - P. M. Anthoni; A. Knohl; C. Rebmann; A. Freibauer; M. Mund; W. Ziegler; O. Kolle; E.‐D. Schulze (Global Change Biology, 2004)
Eddy covariance was used to measure the net CO 2 exchange (NEE) over ecosystems differing in land use (forest and agriculture) in Thuringia, Germany. Measurements were carried out at a managed, even‐aged European beech stand ( Fagus sylvatica , 70–150 years old), an unmanaged, uneven‐aged mixed beech stand in a late stage of development ( F. sylvatica , Fraxinus excelsior , Acer pseudoplantanus , and other hardwood trees, 0–250 years old), a managed young Norway spruce stand ( Picea abies , 50 years old), and an agricultural field growing winter wheat in 2001, and potato in 2002. Large contrasts were found in NEE rates between the land uses of the ecosystems. The managed and unmanaged beech sites had very similar net CO 2 uptake rates (∼−480 to −500 g C m −2 yr −1 ). Main differences in seasonal NEE patterns between the beech sites were because of a later leaf emergence and higher maximum leaf area index at the unmanaged beech site, probably as a result of the species mix at the site. In contrast, the spruce stand had a higher CO 2 uptake in spring but substantially lower net CO 2 uptake in summer than the beech stands. This resulted in a near neutral annual NEE (−4 g C m −2 yr −1 ), mainly attributable to an ecosystem respiration rate almost twice as high as that of the beech stands, despite slightly lower temperatures, because of the higher elevation. Crops in the agricultural field had high CO 2 uptake rates, but growing season length was short compared with the forest ecosystems. Therefore, the agricultural land had low‐to‐moderate annual net CO 2 uptake (−34 to −193 g C m −2 ), but with annual harvest taken into account it will be a source of CO 2 (+97 to +386 g C m −2 ). The annually changing patchwork of crops will have strong consequences on the regions' seasonal and annual carbon exchange. Thus, not only land use, but also land‐use history and site‐specific management decisions affect the large‐scale carbon balance.

Productivity overshadows temperature in determining soil and ecosystem respiration across European forests - I. A. Janssens; H. Lankreijer; G. Matteucci; A. S. Kowalski; N. Buchmann; D. Epron; K. Pilegaard; W. Kutsch; B. Longdoz; T. Grünwald; L. Montagnani; S. Dore; et al. (Global Change Biology, 2001)
Summary This paper presents CO 2 flux data from 18 forest ecosystems, studied in the European Union funded EUROFLUX project. Overall, mean annual gross primary productivity (GPP, the total amount of carbon (C) fixed during photosynthesis) of these forests was 1380 ± 330 gC m −2 y −1 (mean ±SD). On average, 80% of GPP was respired by autotrophs and heterotrophs and released back into the atmosphere (total ecosystem respiration, TER = 1100 ± 260 gC m −2 y −1 ). Mean annual soil respiration (SR) was 760 ± 340 gC m −2 y −1 (55% of GPP and 69% of TER). Among the investigated forests, large differences were observed in annual SR and TER that were not correlated with mean annual temperature. However, a significant correlation was observed between annual SR and TER and GPP among the relatively undisturbed forests. On the assumption that (i) root respiration is constrained by the allocation of photosynthates to the roots, which is coupled to productivity, and that (ii) the largest fraction of heterotrophic soil respiration originates from decomposition of young organic matter (leaves, fine roots), whose availability also depends on primary productivity, it is hypothesized that differences in SR among forests are likely to depend more on productivity than on temperature. At sites where soil disturbance has occurred (e.g. ploughing, drainage), soil espiration was a larger component of the ecosystem C budget and deviated from the relationship between annual SR (and TER) and GPP observed among the less‐disturbed forests. At one particular forest, carbon losses from the soil were so large, that in some years the site became a net source of carbon to the atmosphere. Excluding the disturbed sites from the present analysis reduced mean SR to 660 ± 290 gC m −2 y −1 , representing 49% of GPP and 63% of TER in the relatively undisturbed forest ecosystems.

Productivity of forests in the Eurosiberian boreal region and their potential to act as a carbon sink –‐ a synthesis - E. ‐D. Schulze; J. Lloyd; F. M. Kelliher; C. Wirth; C. Rebmann; B. Lühker; M. Mund; A. Knohl; I. M. Milyukova; W. Schulze; W. Ziegler; A. β. Varlagin; et al. (Global Change Biology, 1999)
Summary Based on review and original data, this synthesis investigates carbon pools and fluxes of Siberian and European forests (600 and 300 million ha, respectively). We examine the productivity of ecosystems, expressed as positive rate when the amount of carbon in the ecosystem increases, while (following micrometeorological convention) downward fluxes from the atmosphere to the vegetation (NEE = Net Ecosystem Exchange) are expressed as negative numbers. Productivity parameters are Net Primary Productivity (NPP=whole plant growth), Net Ecosystem Productivity (NEP = CO 2 assimilation minus ecosystem respiration), and Net Biome Productivity (NBP = NEP minus carbon losses through disturbances bypassing respiration, e.g. by fire and logging). Based on chronosequence studies and national forestry statistics we estimate a low average NPP for boreal forests in Siberia: 123 gC m –2 y –1 . This contrasts with a similar calculation for Europe which suggests a much higher average NPP of 460 gC m –2 y –1 for the forests there. Despite a smaller area, European forests have a higher total NPP than Siberia (1.2–1.6 vs. 0.6–0.9 × 10 15 gC region –1 y –1 ). This arises as a consequence of differences in growing season length, climate and nutrition. For a chronosequence of Pinus sylvestris stands studied in central Siberia during summer, NEE was most negative in a 67‐y old stand regenerating after fire (– 192 mmol m –2 d –1 ) which is close to NEE in a cultivated forest of Germany (– 210 mmol m –2 d –1 ). Considerable net ecosystem CO 2 ‐uptake was also measured in Siberia in 200‐ and 215‐y old stands (NEE:174 and – 63 mmol m –2 d –1 ) while NEP of 7‐ and 13‐y old logging areas were close to the ecosystem compensation point. Two Siberian bogs and a bog in European Russia were also significant carbon sinks (– 102 to – 104 mmol m –2 d –1 ). Integrated over a growing season (June to September) we measured a total growing season NEE of – 14 mol m –2 summer –1 (– 168 gC m –2 summer –1 ) in a 200‐y Siberian pine stand and – 5 mol m –2 summer –1 (– 60 gC m –2 summer –1 ) in Siberian and European Russian bogs. By contrast, over the same period, a spruce forest in European Russia was a carbon source to the atmosphere of (NEE: + 7 mol m –2 summer –1 = + 84 gC m –2 summer –1 ). Two years after a windthrow in European Russia, with all trees being uplifted and few successional species, lost 16 mol C m –2 to the atmosphere over a 3‐month in summer, compared to the cumulative NEE over a growing season in a German forest of – 15.5 mol m –2 summer –1 (– 186 gC m –2 summer –1 ; European flux network annual averaged – 205 gC m –2 y –1 ). Differences in CO 2 ‐exchange rates coincided with differences in the Bowen ratio, with logging areas partitioning most incoming radiation into sensible heat whereas bogs partitioned most into evaporation (latent heat). Effects of these different surface energy exchanges on local climate (convective storms and fires) and comparisons with the Canadian BOREAS experiment are discussed. Following a classification of disturbances and their effects on ecosystem carbon balances, fire and logging are discussed as the main processes causing carbon losses that bypass heterotrophic respiration in Siberia. Following two approaches, NBP was estimated to be only about 13–16 mmol m –2 y –1 for Siberia. It may reach 67 mmol m –2 y –1 in North America, and about 140–400 mmol m –2 y –1 in Scandinavia. We conclude that fire speeds up the carbon cycle, but that it results also in long‐term carbon sequestration by charcoal formation. For at least 14 years after logging, regrowth forests remain net sources of CO 2 to the atmosphere. This has important implications regarding the effects of Siberian forest management on atmospheric concentrations. For many years after logging has taken place, regrowth forests remain weaker sinks for atmospheric CO 2 than are nearby old‐growth forests.